2014
DOI: 10.2341/13-141-c
|View full text |Cite
|
Sign up to set email alerts
|

Patient Age and Dentists' Decisions About Occlusal Caries Treatment Thresholds

Abstract: Objectives This study was performed to (1) quantify dentists’ treatment thresholds for occlusal primary caries; (2) determine if patient's age affects dentists’ decisions to surgically treat these carious lesions; (3) test the hypothesis that patients’, dentists’, and practices’ characteristics are significantly associated with surgical enamel intervention. Methods The study used a cross-sectional design consisting of a questionnaire survey in Japan. This study queried dentists working in outpatient dental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…The result on busyness showed that busier dentists tended to use the clinical practice guidelines more often. This result is consistent with previous analyses of dental practice patterns [25,26], which also demonstrated that busier dentists are more likely to practice evidence-based dentistry.…”
Section: Discussionsupporting
confidence: 92%
“…The result on busyness showed that busier dentists tended to use the clinical practice guidelines more often. This result is consistent with previous analyses of dental practice patterns [25,26], which also demonstrated that busier dentists are more likely to practice evidence-based dentistry.…”
Section: Discussionsupporting
confidence: 92%
“…Dentists' treatment decisions are shown to vary depending on patient characteristics such as age, dental status, caries risk and regularity of attendance [el-Mowafy and Lewis, 1994;Bader and Shugars, 1998;Bader et al, 2001;Gordan et al, 2010;Kakudate et al, 2012Kakudate et al, , 2014. In a low-risk case, dentists may be more liable to defer operative treatment than in patients at high caries risk.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires were distributed to 282 dentists, from whom valid responses were obtained from 189 (67 percent). Demographic characteristics of participants are provided in Table 1 (7,(15)(16)(17)(18). Mean number of years (±standard deviation) since graduation from dental school was 18.5 ± 9.9.…”
Section: Demographic Information Of Participantsmentioning
confidence: 99%